PENGARUH KEADAAN SOSIAL EKONOMI, GAYA HIDUP, STATUS GIZI, DAN TINGKAT STRESS TERHADAP TEKANAN DARAH - Novita Nining Widyaningsih; Melly Latifah (Food and Nutrition Society of Indonesia, 2008)
The objective of this study was to analyze the influential factors of blood pressure. Design of this study was a cross-sectional study. Study was conducted in Bogor, West Java. Criteria’s sample were men, age above 30 years, work as a driver of the public transportation which the routes are Kampus Dalam and Leuwiliang and had been works for more than 2 years. Total sample for this study were 30 people. The result of multiple regression test showed that there were three influential factors of blood pressure. The first factor is family size. Reduction of one family member will raise the systole as high as 2.103 mmHg and diastolic for 1.396 mmHg. The second factor was age. Increasing one year of age will raise the systole for 0.369 mmHg and the diastolic for 0.283 mmHg. The last one was nutritional status. Increasing one unit of BMI will raise the systole for 1.148 mmHg and the diastolic for 1.211 mmHg.